Stereoselective Analysis of Methadone and EDDP in Laboring Women and Neonates in Plasma and Dried Blood Spots and Association with Neonatal Abstinence Syndrome - Metzger, Ingrid F.; Thomas, Anna E.; Evrard, Cindy A.; Jones, David R.; Masters, Andrea R.; Haas, David M.; Haneline, Laura S.; Quinney, Sara K. (American Journal of Perinatology, 2020)
Objective This pilot study evaluated the relationship between maternal and neonatal R- and S-methadone and R- and S-2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) exposure and the severity of neonatal abstinence syndrome (NAS). The use of dried blood spots (DBS) as an alternative for plasma in assessing methadone and EDDP was also assessed.Study Design Women receiving methadone for medication assisted treatment of opioid use disorder during pregnancy were eligible for recruitment. Plasma and DBS samples were collected from mothers during labor, from cord blood, and from newborns during genetic screen. R-/S-methadone and EDDP were measured by high-performance liquid chromatography tandem mass spectrometry (HPLC/MS/MS). Associations between methadone exposure, neonatal morphine requirements, and severity of NAS were examined.Results Twenty women and infants completed the study. Maternal methadone dose at delivery was 112 mg/day (range = 60–180 mg/day). Sixteen neonates experienced NAS requiring morphine; three also required phenobarbital. Higher cord blood concentrations of R-methadone, R- and S-EDDP were associated with higher maximum doses of morphine (p < 0.05).Conclusion Maternal methadone and cord blood concentration at delivery are variable and may be potential markers of neonatal abstinence syndrome.
Keywords: methadone; neonatal abstinence syndrome; opioid use disorder; pharmacokinetics